FORMULASI SEDIAAN EKSTRAK ETANOL BIJI KAKAO (Theobroma cacao L.) SEBAGAI KANDIDAT NATURAL ANTIOXIDANT MELALUI TEKNOLOGI MIKROENKAPSULASI DENGAN METODE SPRAY-DRYING - Purwaningsih, Dewi; Agung A.B, Whyllies; Megaputera, Ireno (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
A research concerning microencapsulation of cacao beans extract by spray drying method with maltodextrin and gum arabic as coating material had been done. The research was aimed to obtain microcapsule formula of cacao bean extract with the best physical characteristic as a natural antioxidant candidate. Microcapsules were prepared by the spray-drying method with a concentration ratio of coating (maltodextrin : gum arabic) and extract. The results showed that the morphology of the microcapsules are spherical concave shaped irregularly. Size distribution shows an average diameter of each of the four formula are the formula I (337 µm), II (356 µm), III (354 µm), IV (371 µm), V (383 µm) and the formula VI (356 µm). Results of quantitative analysis showed that the concentration of total polyphenols (equivalent gallat acid) that trapped in the microcapsules with entrapment efficiency of each are formula I (11.38%), II (11.39%), III (13.77%), IV (10.14%), V (9.59%) and VI (8.80%). The conclusion of this study is the preparation of microcapsules with cacao bean extract with spray-drying method of the sixth formula has good physical characteristics, with the highest entrapment efficiency in this study is the formula III as well as the highest percentage of dissolution in the 60th minutes.Keyword: Microencapsulation, Cacao Bean Extract, Spray-Drying Method